The Student-Athlete Life/Career Portfolio: A Multifaceted Approach to Life and Career Development - Wooten, Jr., H. Ray; Rhyne-Winkler, Martha C. (My University, 1995)
The student-athlete life/career portfolio is a process that developed reflective practice and allowed for an in-depth portrayal of the experiences of each person as an individual and an athlete. The contents of the life/career portfolio provided a unique document that is far more illustrative of an individual's abilities and achievement sthan the traditional resume.
Keywords: models; student development